An Alternative Interpretation of the Recent U.S. Inflation Performance - Mikael Apel; Per Jansson (Sveriges Riksbank, 2000)
An approach to decomposing and interpreting the inflation process is proposed. It suggests that the low U.S. inflation rate in recent years reflects a structural development, but that the low levels of unemployment may be a mainly cyclical phenomenon.
Keywords: C32; E31; 330; Inflation; NAIRU; New economy; Phillips curve; Unobserved-components models